Magnetization and Magnetoresistance of Particulate Sr2FeMoO6 Samples Prepared via Sol-gel Route and Heat Treatment in H2/Ar Atmospheres - Hien, Le Duc; Nguyet, Dao Thi Thuy; Anh, Luong Ngoc; Loan, To Thanh; Duong, Nguyen Phuc; Khoa, Ta Van; Hien, Than Duc (VNU Journal of Science: Mathematics - Physics; Vol 32 No 4, 2016)
Abstract: Double perovskite Sr 2 FeMoO 6 samples were prepared via sol-gel route followed by heat treatment in reduce gas atmosphere of H 2 /Ar (10 vol.% H 2 ) at 900–1100°C for 8 hours. All the samples contain the main phase Sr 2 FeMoO 6 with tetragonal structure (space group I 4/ m ) and a certain amount of secondary phase SrMoO 4 with contents being dependent on annealing temperature. Magnetic properties of the samples were investigated by means of vibrating sample magnetometer (VSM) in temperature range 80–450 K and in magnetic fields of ± 10 kOe. Their magnetoresistance in applied fields of ± 10 kOe was also studied at room temperature. The magnetization data were discussed based on the influence of impurity phase and cation antisite disorder parameter. The magnetoresistance results were analyzed based on the models of spin–dependent electron scattering and electron tunneling through grain boundaries. Keywords : Sr 2 FeMoO 6 , sol-gel, antisite disorder, magnetization, magnetoresistance.